Komparasi Hasil Metode Fuzzy Mamdani dan Tsukamoto untuk Prediksi Produksi Benih Padi (Studi Kasus : Kebun Benih Tunjung Kabupaten Bangkalan) - Elna Diaz Pradini; Edy Santoso; Nurul Hidayat (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Rice is a plant that is cultivated by the government. In order to support the maximum rice production, high-quality rice seeds are needed. One of the certified rice seed producers in Bangkalan Regency is the Tunjung seed garden. The problem with the UPT of Tungjung Bangkalan Regency, when producing certified rice seeds, is that it is difficult to know the exact prediction results using the Ubinan method. To overcome these problems, other prediction methods that is close to accurate are needed. In this study, the Mamdani and the Tsukamoto fuzzy methods are used, which are quite often used to solve prediction problems. This study aims to compare the fuzzy Mamdani and Tsukamoto methods, to find out the best accuracy results based on the smallest MAPE value. Based on the results of the tests that have been carried out, the Tsukamoto method has a better accuracy rate than the Mamdani method. he best results from Tsukamoto's MAPE method, the rainy season and dry season are 0.0%. While the best results from the Mamdani method of MAPE in the rainy season are 13.07% and the dry season is 17.0%.